2016
DOI: 10.1016/j.exer.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

A cellular high-throughput screening approach for therapeutic trans-cleaving ribozymes and RNAi against arbitrary mRNA disease targets

Abstract: Major bottlenecks in development of therapeutic post transcriptional gene silencing (PTGS) agents (e.g. ribozymes, RNA interference, antisense) include the challenge of mapping rare accessible regions of the mRNA target that are open for annealing and cleavage, testing and optimization of agents in human cells to identify lead agents, testing for cellular toxicity, and preclinical evaluation in appropriate animal models of disease. Methods for rapid and reliable cellular testing of PTGS agents are needed to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 67 publications
(103 reference statements)
1
27
0
Order By: Relevance
“…The secondary structure of the full-length hRHO mRNA transcript was analyzed for local folding regions with highly probable and stable secondary structures with substantial (≥8 nt) single-stranded regions. We employed three contemporary algorithms (MFold, SFold, OligoWalk [OW])3032 to predict accessible regions in human RHO mRNA in an established approach developed in this lab, multiparameter prediction of RNA accessibility (mppRNA) 1417,28. A three-dimensional (3D) RNA structure over limited regions can be reliably estimated from a publicly available algorithm called RNA Composer33 (in the public domain, http://rnacomposer.cs.put.poznan.pl); this algorithm draws on published RNA structured elements from the Protein Data Base (repository also for RNA crystal structures).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary structure of the full-length hRHO mRNA transcript was analyzed for local folding regions with highly probable and stable secondary structures with substantial (≥8 nt) single-stranded regions. We employed three contemporary algorithms (MFold, SFold, OligoWalk [OW])3032 to predict accessible regions in human RHO mRNA in an established approach developed in this lab, multiparameter prediction of RNA accessibility (mppRNA) 1417,28. A three-dimensional (3D) RNA structure over limited regions can be reliably estimated from a publicly available algorithm called RNA Composer33 (in the public domain, http://rnacomposer.cs.put.poznan.pl); this algorithm draws on published RNA structured elements from the Protein Data Base (repository also for RNA crystal structures).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that the first major challenge or bottleneck in PTGS development is to identify regions that are accessible 16. We recently reported on a high-throughput screening (HTS) methodologic approach to identify a lead candidate PTGS agent to an arbitrary mRNA target 17. Here, we describe the identification of a lead candidate agent to hRHO mRNA and our initial efforts toward rational optimization.…”
Section: Introductionmentioning
confidence: 99%
“…HhRzs are small RNA molecules causing enzymatic cleavage of polyribonucleotides [128]. The hhRz consists of three helixes surrounding an evolutionary conserved catalytic core.…”
Section: Molecular Therapiesmentioning
confidence: 99%
“…The hhRz consists of three helixes surrounding an evolutionary conserved catalytic core. This gives rise to an antisense complementary region that provides the unimolecular RNA the capacity to recognize and subsequently enzymatically cleave its target mRNA [128].…”
Section: Molecular Therapiesmentioning
confidence: 99%
See 1 more Smart Citation